Beispiel Nr: 06
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(1/0)\qquad Q(-4/0) \\\\ \\ \textbf{Rechnung:} \\ P(1/0)\qquad Q(-4/0) \qquad a=7 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=7(x-1)(x+4)\\ y=7(x^2+x \cdot \left(-1\right) +4\cdot x +\left(-1\right)\cdot 4 )\\ y=7(x^2 +3 x-4) \\ y= 7x^2+21x-28 $